NEED FOR PROSTHETIC TREATMENT IN COMMUNE I OF BAMAKO - Ahmed Ba; Souleymane Samaké; Hapsa Koita; Alphousseiny Touré; Abdoulaye Kassambara; Toumani Sidibé; Bellemkhannate Samira (Romanian Society of Oral Rehabilitation, 2023)
Introduction: Uncompensated dental losses are the cause of functional and aesthetic disorders that require prosthetic treatment. The objective of this work was to assess the dental prosthetic rehabilitation needs of adult patients admitted for consultation in the odontostomatology service of the CSREF of Commune I of the district of Bamako. Materials and methods: our study was descriptive and cross-sectional involving 170 subjects admitted to consultations in the odontostomatology service of the CSREF in commune I of the district of Bamako, of both sexes, of adult age. The principle consisted in carrying out an oral and in particular prosthetic examination of each subject in the cabinet. Statistical analysis used SPSS version 21 software. Results: in the sample, the female sex was in the majority with 57.6% and a sex ratio of 0.73 in favor of men. The most represented missing tooth interval was 1 to 3 teeth with 69.7% of the sample in the maxilla and 71.2% in the mandible. Prosthesis wearers were 38.7% in the maxilla and 15.2% in the mandible. The prostheses worn were suitable in 76.5% of cases. The prevalence of the diagnosed therapeutic need was 62.4% PCP in the maxilla and 67.4% PCP in the mandible. But when the patient is asked to formulate a hypothesis of choice; 67.4% will choose the provisional resin PAP in the maxilla and 68.1% will choose the same type prosthesis in the mandible. The reasons may be due to financial constraints and limited access to oral health services for the poor. Conclusion: a better organization of the socio-health care system could facilitate the accessibility of underprivileged populations to prosthetic rehabilitation.